The Relationship Between Body Mass Index (BMI), Gender and Hypertension With The Incidence of Knee Osteoarthritis at North Lombok Regency Hospital - Aron Baihaqi, Muhammad; Setiarini, Rohmania; Pebruanto, Henry; Sutrisna Wiatma, Deny (International Journal of Health and Pharmaceutical (IJHP), 2026)
Osteoarthritis (OA) of the knee is a degenerative joint disease that often occurs in old age and is one of the main causes of pain and limited mobility. The incidence of knee OA is influenced by various risk factors, including body mass index (BMI), gender, and hypertension, but the results of studies related to these factors still show differences in findings. In North Lombok Regency, data on risk factors for knee OA is still limited. This study aims to analyze the relationship between BMI, gender, and hypertension with the incidence of knee osteoarthritis at North Lombok Regency Hospital. This study uses an analytical observational design with a case control approach. The case group consists of 54 patients who were diagnosed with knee osteoarthritis and underwent treatment at the North Lombok Regency Hospital in the period of July 2024-July 2025. The control group consisted of 54 people who were patients of the Internal Medicine Polyclinic of the North Lombok Regency Hospital in August 2025 who did not suffer from knee osteoarthritis. Sampling of the control group was carried out using purposive sampling techniques based on inclusion and exclusion criteria. Data were obtained from the patient's medical records and analyzed using univariate and bivariate analyses to assess the relationship between independent variables and the incidence of knee OA. he results of this study are expected to show the relationship between BMI, gender, and hypertension with the occurrence of knee osteoarthritis, and to support prevention and treatment efforts for knee osteoarthritis at North Lombok Regency Hospital.